(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of the research is the analysis of the financing of residential real estate in Poland. The paper erected several research problems: how is funded residential real estate market in Poland, how to funding a residential real estate market of Polish influ-ence on the development of the market.To solve research questions were used to study the literature and analysis of statistical data from national statistical sources.